Studies on 2024-T351 Friction Stir Welding joints. - Ali, Aidy; Salit, Mohd Sapuan; Mike, W. Brown (International Science Press, 2009)
Charatterisation of macrostructure, microstructure and precipitate distribution of 2024-T351, aluminium Friction Stir Welding (FSW) joints has been conducted in order to characterise the critical areas for natural fatigue crack initiation. The cyclic strength of the weld micro-regimes are controlled by grain size and distribution of precipitates achieved during the weld process. Tl-re comprehensive information of micro and macro mechanic gathered will be used to assist in understanding the mechanism that governed the fatigue crack initiation, propagation and life of the FSW.